Malaysia on course to become a developed country: prioritizing issues with the analytic hierarchy process - Islam, Rafikul; Ismail, Yusof (The Creative Decisions Foundation, 2010)
By the year 2020, Malaysia aspires to become a fully developed nation. This lofty vision, known as Vision 2020, was unveiled by the former Prime Minister of Malaysia Tun Dr. Mahathir bin Mohamad on February 28, 1991. Currently, it is generally felt that the nation has achieved 50 to 60 percent of the objectives of Vision 2020. What needs to be done to achieve the vision and in what areas? These are the questions that we asked to 759 people living in Malaysia (Malaysians as well as Internationals) in a nationwide survey. As expected, the respondents touched upon a wide variety of issues pertaining to education, economy, technology, quality of life, law and order, R&D, and so on. Upon compilation of all the articulated issues, an affinity diagram was developed.Subsequently, the Analytic Hierarchy Process has been applied in each component of the affinity diagram. This application identifies the main issues that need to be addressed in order to realize the objectives of Vision 2020. The present research findings are expected to provide useful guidelines to the policy makers at the national level in the course of fine tuning Vision 2020 strategies.